HUBUNGAN EFIKASI DIRI DENGAN KETERAMPILAN MENGELOLA KELAS PADA GURU PAUD SE-KECAMATAN TAMBUSAI UTARA KABUPATEN ROKAN HULU - Darma, Surya Puspita; N, Zulkifli; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This study aims to determine the correlation between self efficacy and skills in managing classes for early childhood and teachers in the north tambusai sub district Rokan Hulu. The population of this study is about 43 early childhood and teachers in the North Tambusai sub-district. This study used quantitative correlation to determine the correlation between the independent and dependent variables. Data collecting technique used questioners on likert scale. The result of the test was analyzed by using likert scale trial through IBM SPSS (statistical package for social science) version 21. From the analysis, it was showed that there is a positive correlation between self efficacy and skills in managing classes for early childhood and teachers in the north tambusai sub district Rokan Hulu. It can be seen from the correlation coefficient rxy= 0.378 with significance 0.012<0.05. The category is low with determinant coefficient KD= r2 x 100% = 0,3782 x 100%= 14,29% it is mean that self efficacy influences about 14,29% to the skills in managing classes.Key Word: Early Childhood and Teachers Self Efficacy and Early Childhood and Teachers Skills In Managing Classes